A clinicopathologic and molecular analysis of five cases of bronchiolar adenoma with rare mutations. Issue 5 (2nd March 2022) - Takeda‐Miyata, Naoko; Miyagawa‐Hayashino, Aya; Hamada, Shinshichi; Nagamine, Michiko; Fujii, Tomomi; Imura, Tetsuya; Tsunezuka, Hiroaki; Shimomura, Masanori; Yamaguchi, Tadanori; Yanada, Masashi; Inoue, Masayoshi; Konishi, Eiichi
Abstract: Bronchiolar adenoma (BA) is a rare benign lung tumor that shows proliferation of bland bronchiolar‐type epithelium containing a continuous layer of basal cells. This tumor entity has been newly added to the recent World Health Organization (WHO) classification 5th edition. This entity encompasses a spectrum of lesions: the classic ciliated muconodular papillary tumor (CMPT) and the non‐classic CMPT. Although BA is reported to have driver mutations including BRAF V600E, EGFR, and KRAS, the molecular profile of BA is still incompletely understood. Five resected BAs at our institutions were analyzed. The BA lesions were subdivided into two groups: three proximal‐type BAs and two distal‐type BAs. NRAS codon 12/13 mutation and EML4 exon 20‐ ALK exon 20 fusion were found in two of the three proximal‐types. BRAF V600E mutation was found in one of the two distal‐types. Two cases coexisted with lung adenocarcinoma, with EGFR exon 19 deletion and KRAS mutation, respectively. No recurrence was observed at a median of 12 months (range 2–84 months) of follow‐up. BA has uncommon variants of mutation seen in lung adenocarcinoma. NRAS mutation and ALK fusion partner has not been reported previously. The present cases may reinforce the distinctive biology of BA from lung adenocarcinoma.